The Unequal Consequences of the Covid-19 Pandemic: Evidence from a Large Representative German Population Survey - Lea Immel; Florian Neumeier; Andreas Peichl (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We employ panel data from three waves of a large representative population survey carried out between June and November 2020 to assess in what regards and to what extent different groups of the German population are affected by the COVID- 19 crisis. Using common factor analysis, we demonstrate that people's lives are mainly affected in two ways: First, a notable fraction of the population is concerned that they or their family members and friends may get infected with the coronavirus. Second, many people suffer from socio-economic consequences of the crisis, including a discontinuation of employment, a decrease in household income, and worries about financial troubles. Regressing these two factors on several socio-demographic characteristics reveals that especially the socio-economic consequences vary across population groups. Self-employed persons, marginally employed workers, low-income households, and families with children appear to be burdened over-proportionally.
Keywords: I10; I14; I18; J11; J20; 330; Corona; Covid-19; crisis; pandemic; inequality; Germany